Leveraging single cell analysis and genetic engineering to enhance recombinant AAV production in insect cells - Virgolini, Nikolaus (2023)
"The insect cell-baculovirus expression vector system (IC-BEVS) has been established as an important platform for the manufacturing of therapeutical products, including vectors for gene therapy such as recombinant adeno-associated virus (rAAV). Nevertheless, further characterisation of the underlying biological mechanisms of the IC-BEVS as well as improved engineering strategies are needed to further leverage this system towards optimal product titers and quality. In this thesis, transcriptome analysis approaches (bulk and single-cell) were applied to understand the impact on Sf9 cells of a dual baculovirus co-infection process to produce rAAV. In addition, an improved CRISPR-Cas9 delivery and gene knockout strategy was established to enhance the efficiency of target gene knockout in IC-BEVS."